Manejo da irrigação utilizando umidade do solo e dados climáticos em lavoura de cafeeiro conilon. - Pinheiro, André Alves (2019)
The development and use of irrigation technology has provided benefits to the productive system and avoided possible losses with decreasing water availability, However, problems are observed in most current irrigation projects, such as water waste, rising